Pembuatan Katalis Cu/ZnO/Al2O3 untuk Proses Steam Reforming Metanol menjadi Hidrogen sebagai Bahan Bakar Alternatif - Husin, Husni; Syamsuddin, Yanna (Chemical Engineering Department, Syiah Kuala University, Banda Aceh, Indonesia, 2010)
Study on the use of copper zinc oxide supported on alumina catalyst for steam reforming of methanol to hydrogen has been done. The aim of this work is to study the catalytic properties of copper based catalysts used in the steam reforming of methanol. This method is known as one of the most favorable catalytic processes for producing hydrogen on-board. The catalyst was prepared by impregnation method with Cu loading of 5%, 10%, and 15%,. The X-ray diffraction pattern shows that the catalyst compositions are Cu, CuO, ZnO, and Al2O3. The reactions were carried out in the fixed bed tubular reactor operating at temperatures of 150oC, 200oC, 250oC, 300oC, and 350oC and atmospheric pressure. The product was analyzed using Shimadzu Gas Chromatography GC 8A with mole sieve 5A and porapak-N column 80/100 mesh. The performance of the catalyst shows that the highest methanol conversion was 86% over Cu/ZnO/Al2O3 catalyst with 15% of Cu loading. The selectivity and yield of hydrogen was 66% and 57% respectively over Cu/ZnO/Al2O3 catalyst with 15% of Cu loading. Selectivity of carbon dioxide is 18% over Cu/ZnO/Al2O3 catalyst with 15% of Cu loading at 300oC.Keywords: alumina oxide catalyst, copper zinc oxide, hydrogen, impregnation